Konsepsi Trust yang Dibangun Etnis Tionghoa dalam Politik Di Kota Tanjungpinang Provinsi Kepulauan Riau - Darmawan, Eki (Kemudi, 2016)
Trust is an expectation that a person can be trusted in all relationships, demonstrate consistent and predictable behavior. Trust owned predictions related to gains and losses will result because these choices. Presentation concept of trust is very important to understand the issues of transparency and accountability networking interaction of the actors in governance. Some have argued the importance of trust in governane networking. First, in setting the theory of governance, the concept of trust into one keywords in it. Second, network governance as key words to make the trust as the foundation of the building.Third, the principle of transparency and accountability of governance actors is strongly associated with the concept of trust, where trust becomes the purpose of the implementation of these two principles. Various opinions of scientists put trust as the foundation, pillars and social capital in networking and building effective governance, so it is important to understand the concept of trust in the context of network and governance. Confidence (trust)is the basic element of relations between the actors and the social structure of the network, so the trust manifested in the form of building the network. Social capital makes the trust as an integral part even be the main pillars of social network system. The socialist social system built with the advent integrity of a particular ethnic, one of them ethnic Chinese in Kepulauan Riau, Especially Tanjungpinang. It was built in Tanjungpinang are ethnic Chinese with identity politics and ethnic politics they controlled sectors of the economy, education, culture, and religion is so strong that formed Hight-Trust.